(untitled) (Journal of Informatics and Mathematical Sciences, 2019)
In this paper, we propose and analyze a generalized \(α\)-nonexpansive mappings on a nonempty subset of a hyperbolic space i.e., align* 12d(x,Tx)≤ d(x,y)d(Tx,Ty)≤ α d(y,Tx)+α d(x,Ty)+ (1-2α)d(x,y), align* and prove \(Δ\)-convergence theorems and convergence theorems for a generalized \(α\)-nonexpansive mappings in a hyperbolic space.